How to build an optimized movement analysis laboratory for high Performance athletes of various sport disciplines - Janhen, L. (The Engineering of sport 7, Volume 1, 2008)
Movement analysis plays an important role for both, enhancing athletes' performance and movement techniques in various sport disciplines as well as optimising sport equipment. Therefore an optimal movement analysis laboratory should provide most realistic conditions for a variety of sport disciplines, such as track and field, gymnastics and team sports as well as for testing sport equipment ranging frorn sport shoes, floor constructions, landing mats, apparatus for gymnastics and throwing objects like balls, discs or javelins. The purpose of this paper is to demonstrate the functional and technical requirements for an optimized movement analysis laboratory. Special emphasis is given to the constructive properties and the spatial restrictions imposed by highly accurate measurement devices for both, motion capture and ground reaction forces without interfering with the performance of the athletes. As an example for a state-of-the-art movement analysis laboratory the new constructed lab of the Centre for Sport Science and Sport Medicine is presented. The requirement analysis included location factors, demands of actual and future research projects in sport science and medicine, physical education, sport associations and industrial partners. In addition important Information for the planning process including key positions and a general timeline are presented. From these data, recommendations how to plan and build a movement analysis laboratory are derived.